Letter from the United States Office of War Information to Ernst Berl, April 6, 1944 - United States. Office of War Information (1944)
Letter from W. O. Somin of the United States Office of War Information to Ernst Berl (1877-1946) requesting a description, in German, of Berl's invention that "turns 'farm wastes' into gasoline."
Keywords: Berl, Ernst, 1877-1946; United States. Office of War Information; World War (1939-1945); Waste products as fuel; Biomass energy